The rationality of Human Rights: between the Legal System and Human Sciences - Manzi, Adrian (Nómadas. Critical Journal of Social and Juridical Science, 2008)
.- This paper aims at thinking about how Human Rights influence the knowledge-power relations, by allowing both the objectivation and subjectivation of man, and by emphasizing the relationship they bear to the role of government, which is to conduct the conducts of the population. The course notes from the College de France delivered by Michel Foucault between 1975 and 1978 are taken as a reference to write the present work. It is possible to say that, thought of as helpers of the system of disciplinary power and as a technique able to group a shapeless mass of people, Human Rights meet the requirements that enable the government to take care of its population in the best possible way, or – at least – to know some aspects of its dynamics in biological terms. In order to analyze what types of subjectivities are promoted from a previously established objectivity, it is necessary to know the mechanisms and the logic, the tactics and the techniques with which power operates in this society. It is likewise necessary to know the characteristic features that power has in relation to situations where subjects are involved in intrinsic movements of the population. Human Rights organizations start their action right where there is an event, either individual or collective. Obviously, this is a series directly linked to the international and national legal discourses, which triggers the knowledge (savoir) about man, about this collectivity. There are certain situations characteristic of society which allow thinking and analyzing the ways in which a subject could have been inserted into the games of truth as an object, that is to say, in relationships where there is a kind of “game of truth”. This is exactly when objectivation and subjectivation are possible –the moment man is determined to observe himself as a space and mastery of knowledge (savoir), and also as the making of things. Human sciences have enriched the aspects mentioned in the previous paragraphs; they have “oxygenated” the relations of disciplinary power, oppression, surveillance, medicalization, education, and politics (in general). Human Rights have operated in a coercive way towards the penitentiary, medical and judicial knowledge (savoir). Human Rights add air when the relationships are about to collapse. Do not only they promote subjectivity and political activity, but also make power relations dynamic.